Video communication, blue marble awe, and attitudes toward climate change and renewable energy - Ion Bogdan Vasi; Mario Paez-Arellano (npj Climate Action)
Abstract We conducted a survey experiment to examine how respondents’ attitudes toward climate change and renewable energy are affected by six communication approaches using online videos. Three interventions used single message approaches, which focused on facts about climate change science, facts about solar PV technology, or the emotion of blue marble awe (the feeling of awe for the Earth arising from the realization that we live on a fragile planet). Two interventions used dual message approaches, which combined blue marble awe with either climate change science or solar PV technology facts. One intervention used a dual reinforced message approach, which combined blue marble awe, solar PV technology facts, and a message from an astronaut who is an ambassador for renewable energy. Results show that the dual reinforced message approach has the strongest effects on energy and environmental attitudes. Our findings offer important lessons for scientists and educators interested in energy communication.